Impact of Parental Vaccination Status on Yellow Fever Vaccination in Children Aged 0–1 Years in the Democratic Republic of Congo: Mixed Sequential Explanatory Study - Abraham Mukongo Bulaimu Lukeba; Gerard Eloko Eya Matangelo; Simon-Decap Mabakutuvangilanga Ntela; Monique Rothan- Tondeur; Rita Georges Nohra (BioScientific Review, 2025)
Background. Yellow fever occurs in the intertropical regions of Africa and South America. Vaccination is a simple, effective, and inexpensive means to reduce morbidity and mortality from infectious diseases. Presently, the world is witnessing a decrease in the number of children vaccinated each year in low-income countries and in the Democratic Republic of the Congo (DRC). This scenario is leading towards concrete consequences and even a resurgence of vaccine-preventable infectious diseases.Methodology. This is a sequential and explanatory study conducted using a mixed-method approach. The quantitative component, of the retrospective, multicenter, analytical type, was carried out using data from the post-campaign yellow fever coverage study in 8 concerned provinces. Whereas the qualitative component, of the descriptive phenomenological type, was carried out through semi-directive interviews held with the heads of household of children aged 0-1 year in Tshuapa Province. Quantitative data was analyzed using SPSS (version 25) and qualitative data was analyzed using ATLAS-Ti 22 software.Results. Quantitative analysis showed that there was a statistically significant influence of the household head's vaccination status on the routine vaccination of children aged 0–1 year, with a chi-square test indicating χ2=62.706 and p=0.000. This means that children whose parents are immunized are more likely to be immunized as well. Despite this positive influence, the study revealed that 27.7% of immunized children had parents who were themselves immunized. This figure raises concerns about the effectiveness of awareness campaigns and parental decision-making on immunization. Qualitative analysis highlighted several factors influencing parental decision to vaccinate including parents' knowledge of vaccination, their positive experiences with it, and their sense of parental responsibility.Conclusion. These results highlight not only the importance of household heads' vaccination status in the child immunization process, however, also the need to address concerns related to immunized children, even in households where parents are immunized. Therefore, national authorities must develop effective strategies to improve immunization coverage and raise family awareness regarding the importance of vaccination.